Historical review of the research on the fossil mollusks from Corumbataí formation, Paraná Basin, Brazil - Salvador, Rodrigo B.; Simone, Luiz R. L. (Revista da Biologia, 2018)
The Corumbataí Formation belongs to the Passa Dois Group in Paraná Basin, Brazil, and dates from the end of the Paleozoic Era, more precisely from the (Upper) Permian Period. The Formation’s fossil record, which is composed mainly of bivalve mollusks, has begun to be studied at the first decades of the 20th century. At first, the research was primarily conducted by foreigner paleontologists; only by the 1940’s Brazilian scientists joined them in the study of the Formation, which was conducted until the beginning of the present decade. Despite the intense research, the study on some topics such as systematics remains incomplete.